Numerical schemes for 3D parabolic problem with non-local boundwy condition - Čiegis, Raimondas; Meilūnas, Mečislovas; Subač, Olga (Lietuvos matematikos rinkinys, 2004)
Two finite difference schemes are used to solve the 3D parabolic problem with a non-local boundary condition. A new approximation of the initial condition is proposed for the explicit Euler scheme. Error estimates in the maximum norm are obtained and results of some numerical experiments are presented. The second scheme is based on implicit splitting method. An efficient realization algorithm of the LOD scheme is proposed.